2005
DOI: 10.1017/s1355617705050745
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-referenced validity of a neuropsychological test battery: Equivalent performance in elderly Hispanics and Non-Hispanic Whites

Abstract: This study examined the validity of the Spanish and English Neuropsychological Assessment Scales (SENAS) in comparison with clinical diagnosis of normal cognition versus cognitive impairment, not demented (CIND) versus demented in elderly Hispanics and Whites. Relationships between SENAS scales and diagnosis were essentially the same in Hispanics and Whites. Verbal memory measures were most strongly related, with more than 35% of the variance in these measures accounted for by diagnosis independent of effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 36 publications
1
86
1
Order By: Relevance
“…The final diagnosis was the consensus decision established at a multidisciplinary case conference. A previous study showed that neuropsychological test results were equally related to clinical diagnosis in whites and Hispanics in this sample (Mungas et al, 2005).…”
Section: Subjectsmentioning
confidence: 47%
“…The final diagnosis was the consensus decision established at a multidisciplinary case conference. A previous study showed that neuropsychological test results were equally related to clinical diagnosis in whites and Hispanics in this sample (Mungas et al, 2005).…”
Section: Subjectsmentioning
confidence: 47%
“…45,46 A series of stimuli is presented on the computer screen visually (object) and orally (spoken name), 1 at a time. Participants are instructed to repeat the stimuli to the examiner in order of size, from smallest to largest.…”
Section: Nih-tb List Sorting Working Memory Test (Working Memory)mentioning
confidence: 99%
“…The prototype task has been previously validated in an elderly sample. 45,47 The List Sorting task takes approximately 7 minutes to administer. Test scores consist of total items correct across all trials.…”
Section: Nih-tb List Sorting Working Memory Test (Working Memory)mentioning
confidence: 99%
“…In the current study, we report preliminary data suggesting that bilingualism also affects naming scores in older bilinguals. It is important to determine how bilingualism affects naming in this population because older adults are frequently referred for neuropsychological evaluation and because confrontation naming is commonly used to diagnose cognitive status (e.g., naming scores improve discrimination of dementia from other forms of cognitive impairment; Mungas et al, 2005). To this end, we investigated whether older bilinguals would show the either-language scoring effects previously reported in college-aged bilinguals (Kohnert et al, 1998).…”
Section: Introductionmentioning
confidence: 96%